Neuroprotective effects of Neurotrophin-3 in MPTP-induced zebrafish Parkinson’s disease model - Omar, Noor Azzizah; Kumar, Jaya; Teoh, Seong Lin (Frontiers in Pharmacology, 2023)
Introduction: Neurotrophin-3 (NT3) is a neuroprotective growth factor that induces the development, maintenance and survival of neurons. This study aims to localize NT3-expressing cells in the adult zebrafish brain and examine the role of NT3 in a zebrafish Parkinson's disease (PD) model.Cellular localization of NT3 in adult zebrafish brains was conducted using in situ hybridization. Subsequently, adult zebrafish were injected intraperitoneally with 100 µg/g of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and treated with 400 ng/g body weight of recombinant NT3 (rNT3) via intracranial injection 24 hours following MPTP injection. The fish were assessed for neurobehavioral, gene expression, immunohistology, and protein analysis on days 3, 5 and 10 post-MPTP injection.Results: Our findings showed that NT3 was extensively expressed throughout the adult zebrafish brain in neurons. Administration of rNT3 has significantly improved the locomotor activity, with upregulation of th1, dat, ntf3 and bdnf gene expressions, compared to MPTP-induced zebrafish. Dopaminergic neurons were also significantly increased significantly in the zebrafish brain following rNT3 treatment. ELISA analysis reported raised GST and decreased caspase-3 levels on day 3 of assessment. The trophic changes of rNT3, however, decline as the assessment day progresses.This study is the first one of the earliest the first to examine the role of NT3 in the adult zebrafish PD model. NT3 has remarkable trophic effects in the zebrafish PD model. However, further study is needed to examine the dosage requirements and long-term effects of NT3 in PD.